2022
DOI: 10.3389/fcell.2022.814949
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Transplantation of Human Hair Follicle-Derived Mesenchymal Stem Cells Ameliorates Trabecular Bone Loss in Osteoporotic Mice

Abstract: Background: Hair follicles harbor a rich autologous stem cell pool and human hair follicle-derived mesenchymal stem cells (hHF-MSCs) have multi-lineage differentiation potential. Many sources of MSCs include hHF-MSCs have been attractive candidates for cell therapy, regenerative medicine and tissue engineering. The present study is to explore the effect of intravenous transplantation of hHF-MSCs on bone mass in osteoporotic mice and its mechanism, and provides prospects for clinical applications for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…For osteoclastogenesis assays, we isolated BMMs from 6week-old C57BL/6N mice and cultured them in complete minimum essential medium eagle alpha modifications (α-MEM) medium with M-CSF (30 ng/ml) and RANKL (50 ng/ ml) for 7 days as described previously (63). In brief, the femurs and tibias of 6-week-old mice were surgically removed, and the bone marrow was flushed out with warm, serum-free α-MEM medium using a 1 ml syringe.…”
Section: Isolation Of Bmms Cell Culture and Differentiationmentioning
confidence: 99%
“…For osteoclastogenesis assays, we isolated BMMs from 6week-old C57BL/6N mice and cultured them in complete minimum essential medium eagle alpha modifications (α-MEM) medium with M-CSF (30 ng/ml) and RANKL (50 ng/ ml) for 7 days as described previously (63). In brief, the femurs and tibias of 6-week-old mice were surgically removed, and the bone marrow was flushed out with warm, serum-free α-MEM medium using a 1 ml syringe.…”
Section: Isolation Of Bmms Cell Culture and Differentiationmentioning
confidence: 99%
“…277 Therefore, EVs containing paracrine factors, which are isolated from MSC conditioned medium, offer a strategy for cell-free MSC therapy. 278,279 Several studies have shown that human-derived MSCs can enhance osteogenesis and prevent OVX-mediated bone loss in mice, [280][281][282] but the specific mechanism is unclear. Wang et al 283 analyzed the metabolomics of mice that received BMSC transplantation, suggesting that exogenous BMSC may play an anti-osteoporosis role by maintaining estrogen levels to mediate adipogenesis and osteoblastic metabolism in bone.…”
Section: Stem Cell-based Therapymentioning
confidence: 99%
“…Several studies have shown that human‐derived MSCs can enhance osteogenesis and prevent OVX‐mediated bone loss in mice, 280–282 but the specific mechanism is unclear. Wang et al 283 .…”
Section: Anti‐osteoporosis Therapiesmentioning
confidence: 99%